Immobilization of per- and polyfluorinated alkyl substances (PFAS) from field contaminated groundwater by a novel organo-clay vs. colloidal activated carbon under flow conditions - Gunarathne, Viraj; Melo, Tatiane Medeiros; Schauerte, Marina; Groth, Felix; Slaný, Michal; Rinklebe, Jörg (Journal of hazardous materials, 2025)
Two novel and unique adsorptive materials, one (Fluorolock®) from clay mineral sepiolite coated with the cationic polymer polydiallyldimethylammionium chloride (pDADMAC) and the other (Intraplex®) from colloidal activated carbon were specially developed for the in situ remediation of per- and polyfluoroalkyl substances (PFAS) in the saturated zone. We evaluated the potential of both materials to immobilize PFAS in soils under flow conditions via soil column experiments using groundwater, which was contaminated with PFAS in the field. Furthermore, the potential ecotoxicological effects of both materials on aquatic organisms were assessed by exposing the soil column effluent to Daphnia magna. Soils amended with Fluorolock® and Intraplex® led to a significant reduced leaching of PFAS. Intraplex® had higher PFAS immobilization efficiency than Fluorolock® likely due to its higher carbon content (84 % higher than Fluorolock®) and larger specific surface area (93 % higher than Fluorolock®). Fluorolock® and Intraplex® resulted in changes in water parameters, however, the effluent from soil amended with Fluorolock® exhibited mild toxicity, whereas the amended with Intraplex® was not toxic to D. magna. The distinct PFAS immobilization and the respective toxicity outcomes, with Fluorolock® showing mild toxicity and Intraplex® exhibiting no toxicity to D. magna, indicate that Fluorolock® and Intraplex® could be suitable for the remediation of groundwater contaminated with PFAS.
Keywords: Daphnia magna; podzemní voda; Groundwater; Immobilization; Daphnia; Aluminum Silicates; jíl; zvířata; Aquifer; Clay; Carbon; Environmental Restoration and Remediation; Adsorption; Water Pollutants, Chemical; Colloids; regenerace a remediace životního prostředí; Animals; silikáty hliníku; fluorokarbony; adsorpce; uhlík; Remediation; Fluorocarbons; Charcoal; dřevěné a živočišné uhlí; chemické látky znečišťující vodu; koloidy